Two-Stage Treatment of Enterocutaneous Fistulas - V. Yu. Struchkov; S. V. Berelavichus; E. A. Akhtanin; D. S. Gorin; M. V. Dvukhzhilov; A. A. Goev; A. I. Burmistrov; P. V. Markov; A. G. Kriger (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to determine the most efficient treatment of enterocutaneous fistulas.Materials and methods. Eighty-eight patients with intestinal fistulas underwent a two-stage treatment, including: the first stage — multicomponent therapy, the second stage — reconstructive surgery. Enterocutaneous fistulas were diagnosed in 61 patients, enteroatmospheric fistulas — in 26 patients, and combined fistula (enterocutaneous and enteroatmospheric) — in 1 patient.Results. All 88 patients underwent reconstructive surgery after the multicomponent therapy. Resection of the intestine with a fistula with the formation of an entero-entero anastomosis was performed in 72 (81.8 %) patients; marginal resection of the intestine with a fistula, followed by suturing of the defect — in 7 (8.0 %); resection of the intestine with fistulas in combination with excision and suturing of the fistula — in 5 (5.7 %); an operation aimed at disabling the fistula from the passage of intestinal contents — in 3 (3.4 %); resection of the intestine with a fistula in combination with fistula exclusion — in 1 (1.1 %) patient. Postoperative complications in the group of patients with enteroatmospheric fistulas occurred in 13 cases, in the group with enterocutaneous fistulas — in 25 patients. Three (3.4 %) patients with enterocutaneous fistulas died from complications unrelated to the underlying disease and surgical interventions.Conclusion. Two-stage treatment including multicomponent therapy (nutritional support, infection generalization control, local wound treatment) and reconstructive surgery allowed to reduce mortality rates to 3.4 %, which proves the effectiveness of this method.